Teologi Kemaslahatan Social-Phsycal Distancing dalam Penanggulangan Covid-19 - Hannan, Abd Hannan; Wafi Muhaimin; Subairi (LPPM IAIN Parepare, 2020)
This article discusses the maslahah of COVID-19 mitigation, particularly in the application of social-physical distancing in terms of theological perspective. There are three main problems examined in this study, namely; COVID-19, benefit, and social-physical distancing. Using this type of qualitative research based on the theory of maqashid al-shari'ah, this study found that both social and physical distancing is a form of COVID-19 mitigation that both emphasizes distance protection through protection and preservation activities. In practice, social distancing and phsycal distancing function to present goodness and usefulness (maslahah) and to avoid bad things (mudharat). From a telogical perspective, the function of usefulness and goodness in the enactment of the rules of social distancing and physical distancing, it has the same content as the principle of the benefit of the theory of maqashid al-shari'ah. In maqashid al-shari'ah, an application of Islamic law must contain the purpose of benefit, where this benefit is measured based on three aspects; aspects of the scope of the maslahah, aspects of its influence, and finally are aspects of the strength of the proposition. Although the benchmarks vary, but in substance the three must contain the guiding principle on five things, namely; the safeguarding of religion, life, descent, intellect, and finally the preservation of property.